2014
DOI: 10.1155/2014/690103
|View full text |Cite
|
Sign up to set email alerts
|

Current and Emerging Biomarkers of Cell Death in Human Disease

Abstract: Cell death is a critical biological process, serving many important functions within multicellular organisms. Aberrations in cell death can contribute to the pathology of human diseases. Significant progress made in the research area enormously speeds up our understanding of the biochemical and molecular mechanisms of cell death. According to the distinct morphological and biochemical characteristics, cell death can be triggered by extrinsic or intrinsic apoptosis, regulated necrosis, autophagic cell death, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 110 publications
1
29
0
1
Order By: Relevance
“…Cell cycle and death (apoptotic and non-apoptotic) regulators play crucial roles in normal tissue physiology as well as in pathological processes such as oncogenesis and inflammation [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Cell cycle regulation is achieved through a family of serine/threonine kinase holoenzyme complexes consisting of regulatory cyclin that bind to and activate catalytic cyclin-dependent kinases (CDKs) [1].…”
Section: Introduction Cell Cycle and Deathmentioning
confidence: 99%
See 4 more Smart Citations
“…Cell cycle and death (apoptotic and non-apoptotic) regulators play crucial roles in normal tissue physiology as well as in pathological processes such as oncogenesis and inflammation [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Cell cycle regulation is achieved through a family of serine/threonine kinase holoenzyme complexes consisting of regulatory cyclin that bind to and activate catalytic cyclin-dependent kinases (CDKs) [1].…”
Section: Introduction Cell Cycle and Deathmentioning
confidence: 99%
“…The loss of plasma membrane integrity during necrosis leads to the leakage of intracellular contents, some of which, such as high mobility group protein B1 (HMGB1) and hepatoma-derived growth factor (HDGF), evoke an inflammatory response [5,6,11,15,16]. Necrosis has been traditionally regarded as unregulated, but recent studies revealed a form of regulated necrosis which, with respect to its dependence on specific signaling pathways, was divided into necroptosis, mitochondrial permeability transition-dependent regulated necrosis and parthanatos [5,6,11,[15][16][17]. Necroptosis can be triggered in response to various factors (e.g., alkylating DNA damage, ligation of death receptors such as TNFa, FasL and TRAIL which may activate apoptosis), especially if the caspases (and in particular caspase 8) are inhibited by genetic manipulations (e.g., by gene knockout or RNA interference) or blocked by chemical inhibitors [6,11,15,16].…”
Section: Introduction Cell Cycle and Deathmentioning
confidence: 99%
See 3 more Smart Citations